Challenges and technical aspects in the management of muscle invasive bladder cancer as retrograde radical cystectomy with ileal conduit - Nadeem Bin Nusrat,; Assad Ur Rehman,; Nauman Zafar,; Shujah Muhammad,; Sarmad Imtiaz Bajwa,; Imtiaz, Saira (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate long-term outcomes in patients homogenously treated with radical cystectomy and ileal conduit for muscle invasive bladder cancer. Method: The retrospective study was conducted at the Urology Department of Pakistan Kidney and Liver Institute and Research Centerm, Lahore, Pakistan, and comprised data from December 25, 2017, to January 16, 2023, related to patients who underwent radical cystectomy with ileal conduit with or without neo-adjuvant and adjuvant radiation, chemotherapy, or immunotherapy for papillary urothelial carcinom of the bladder. Clinical trajectory, histopathological characteristics and long-term clinical outcomes were noted. Data was analysed using SPSS 20. Results: In our study of 40 patients with muscle invasive bladder cancer, males predominated (32, 80%), with a median age of 57.4 years (IQR: 29-80). Diagnosis was early in 5 patients (12.5%) with varying hematuria durations, while 34 patients (85%) had a smoking history. Comorbidities included hypertension in 17 patients (42.5%), diabetes in 1 patient (2.5%), both hypertension and diabetes in 9 patients (22.5%), and a combination of hypertension, diabetes, and ischemic heart disease in 3 patients (7.5%). Transurethral resection was performed once in 13 patients (32.5%) and multiple times in 27 patients (67.5%). Additionally, 5 patients (12.5%) received immunotherapy, 11 patients (27.5%) underwent non-adjuvant radiation, and 14 patients (35%) received non-adjuvant chemotherapy. Papillary urothelial carcinoma was the predominant histological subtype among 37 (92.5%) patients. Patients receiving chemotherapy had significantly better overall survival (p=0.02).No significant differences were noted in recurrence or survival by therapy modality (p>0.05). These findings highlight the significance of early diagnosis, tailored treatments, and comorbidity management in muscle invasive bladder cancer patients. Age stratification revealed significant survival differences across groups (X² = 10.923, df = 3, p = 0.012). Analysis by complications did not show age-related survival variations (X² = 3.978, df = 3, p = 0.264). Conclusion: Achieving excellent long-term survival in MIBC patients requires a multidisciplinary approach, emphasizing early diagnosis, tailored treatment, and adherence to guidelines and protocols. Key Words: Radical cystectomy, Ileal conduit, Management, Muscle invasive bladder cancer, Papillary urothelial carcinoma.